Financial technology (Fintech) research trend: a bibliometric analysis - Johan Ariff Jafri; Syajarul Imna Mohd Amin; Aisyah Abdul Rahman (Discover Sustainability)
Abstract Fintech enables the digitalisation of financial services to acquire a competitive edge and aid decision-makers in making better decisions for businesses. Fintech development has piqued the interest of many scholars exploring its opportunities, threats, and implications for market players and consumers. This study aims to provide a bibliometric analysis, content analysis and direction for future research based on the review of 3884 Fintech manuscripts from the Scopus database (1986–2024). The bibliometric analyses include publication year, source type, subject area, keyword analysis, geographical distribution, authorship, active institutions, and citation analysis. The content analysis explores Fintech publication trends and recent issues. The soaring Fintech research since Fintech 3.5 (after 2015) indicates its critical relevance for theoretical and practical implications. The findings highlight: (1) the most influential Fintech articles, authors, journals, institutions, and countries; (2) Fintech dimensions for banking and non-banking; and (3) recent Fintech issues related to systemic risk, security, and trust. The study serves as a guide for future research in building a theoretical framework and research context.